Ownerâs Support, IT Sophistication and IT Adoption in Indonesian Manufacturing SMEs - Singgih Saptadi; Iman Sudirman; T.M.A Ari Samadhi; Rajesri Govindaraju (LPPM ITB, 2015)
The importance of technology, especially information technology (IT), to businesses is widely accepted. But, different from large enterprises, small and medium enterprises (SMEs) with their limited resources adopted IT slowly. Literature on technology adoption suggests that organizational readiness is one of many factors that determine the adoption of technology. This paper relates IT adoption in Indonesian manufacturing SMEs with their IT readiness represented by owners support and IT sophistication they have. In this paper, the variety of IT adoption by SMEs was explored using business process approach. The support from SMEs owner represented by ownerâs IT knowledge and resource allocation. IT sophistication included management level supported by IT, IT skill and IT innovativeness of SMEs staff. Three propositions were formulated and explored using data collected from 320 SMEs. Using cluster analysis, these SMEs were classified into five type of IT adoption based on three business focus (supplier, internal and customer): early adoption, internal focus adoption, customer focus adoption, internal-customer focus adoption and balanced adoption. The results suggests wider IT adoption requires greater support from the owner and higher IT sophistication.